Anailisis Dengan Indikator Bollinger Band dan Stochastic Oscillator Pada Saham Serta Fundamental Perusahaan LQ 45 Sub Sektor Perbankan - Puji Astutik; Jeni Susyanti (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
This research aims to compare the level of return and decision making at the right time to sell and buy shares in Banking Companies listed on the LQ45 index. The technical indicators used are Bollinger Band and Stochastic. The data used is secondary data, with a sample of shares of banking sub-sector companies listed on the LQ45 index for the period April 2023 - April 2024. Sampling was carried out using a purposive sampling technique. Data collection uses TradingView Software on the TradingView.com site. Based on research results from the Bollinger Band and Stochastic indicators. What produces bigger profits is to use the Stochastic Oscillator. Currently, a buy signal will appear when the K% line crosses the D% line from top to top in the Oversold zone which is confirmed by the stochastic line cutting to the vertical scale 20, this situation is called the Golden Cross (buy moment) for the reason that the price will soon rise. Meanwhile, a sell signal will appear when the K% line crosses the D% line from top to bottom in the overbought zone which is confirmed by cutting the stochastic line to a vertical scale of 80, this situation is called a Death Cross (selling moment) for the reason that the price will soon fall. The results of this research is that the Sthocasstiic indicator provides better results and Net Profit has an effect on share prices.